GURU DUA ZAMAN : Kajian terhadap KehidupanSosialEkonomiGuru di IndonesiaTahun 1967 - 2010 - Dewi, Hasanah Ratna (2015)
Penelitianiniberawaldarikeresahanpenelitidalammelihatberbagaipermasalahansosialdanekonomi yang dihadapiolehpara guru sejakmasaOrdeBaruhinggaReformasi.Berbagaidinamikadalamduniapendidikanikutmempengaruhiperan guru di dalamnya, sehinggamenimbulkanketertarikanpenelitiuntukmengkajimengenaikehidupansosial, ekonomidanpendidikan guru yang tertuangdalamsebuahkaryailmiahberjudul"GURU DUA ZAMAN: KajianterhadapKehidupanSosialEkonomi Guru di Indonesia Tahun 1967-2010". Masalahutama yang diangkatdalamskripsiiniadalah"BagaimanaPerkembanganKehidupan Guru di Indonesia Tahun 1967-2010?".Permasalahanutamatersebutkemudiandibagikedalambeberapapertanyaanpenelitianyaitu : (1) Bagaimanasistempendidikan guru di Indonesia padamasaOrdeBaru ? (2) Bagaimanasistempendidikan guru di Indonesia padamasaReformasi? (3) Bagaimanakehidupansosialekonomi guru di Indonesia padamasaOrdeBaru? (4) Bagaimanakehidupansosialekonomi guru di Indonesia padamasaReformasi?Untukmengkajipermasalahantersebutpenelitimenggunakanmetodehistoris, meliputiheuristik, kritik, interpretasidanhistoriografi.Berdasarkanhasilkajiandapatdijelaskanbahwa Guru menjadiprofesimuliadalammencerdaskankehidupanbangsanamunnasibpara guru sendiritidakpernahmengalamiperbaikanselamamasaOrdeBaru. MemasukimasaReformasibarulahterjadiperubahanterhadapnasib guru.PuncaknyaialahdengandikeluarkannyaUndang-Undang Guru danDosenNomor 14 Tahun 2005 denganadanya program sertifikasi guru, sehinggamenjadikanadanyaperubahanterhadapkehidupansosialekonomi guru.Penelitianinidiharapkandapatbermanfaatbagipara guru, masyarakat, pemerintahmaupunbagipembelajaran di sekolah. This study is started from researcher anxiety in seeing various social and economic problems faced by teachers in New Order era until Reformation. Various dynamics in education field also influence teacher role in it, so invoke researcher interest to examine teacher's social, economy and education life which cast into a scientific work titled "TWO ERA'S TEACHER: A Study Toward Social Economic Life of Teacher in Indonesia in Year of 1967-2010". The main problem which is posed in this paper is "How Did The Development of Teacher's Life in Indonesia in Year of 1967-2010?" That main problem then divided into several research questions, namely: (1) How the system of teacher education in Indonesia in New Order? (2) How the system of teacher education in Indonesia in Reformation era? (3) How teacher's social economic life in Indonesia in New Order era? (4) How teacher's social economic life in Indonesia in Reformation era? To examine that problem, researcher use historical method comprising heuristic, critic, interpretation and historiography. Based on the result of that examination it can be explained that Teacher is lofty profession in developing nation life but the destiny of teachers themselves never experience improvement during New Order. Entering Reformation era, the change toward teacher destiny started to happen. The peak is the issuing of Teacher and Lecturer Act No.14 Year of 2005 by the existence of teacher certification program, so bring the change toward teacher's social economic life. It is hoped that this study can beneficial for teachers, community, government and also for learning in school.